Optimism and Academic Resilience: Antecedents of Subjective Well-Being in Working Students - Dewi, Ros Patriani; Lekahena, Femmy (Universitas Negeri Makassar, 2025)
Students who work have subjective well-being that is unstable or even tends to decrease due to the negative impact felt by students which will influence the subjective well-being of working students. The factors that can affect subjective well-being in students are academic resilience and optimism which will be examined in this study. The aim of this research is to prove empirically about the influence optimism and academic resilience on subjective well-being. 100 working students in UMBY was taken as participant using convenience sampling technique. Data collection was carried out by using Subjective Well-Being Scale, Optimism Scale, and Academic Resilience Scale. The data generated through the data collection process was analyzed using multiple linear regression tests. The research results show that optimism and academic resilience have a positive effect on subjective well-being, both simultaneously and partially. The effective contribution of optimism and academic resilience is 32,5%, while 67,5% is influenced by other variables not examined in this research.